BREAKTHROUGH UNDER TRANSFORMATION AND REGULATION: EXPLORING THE DEVELOPMENT OF ENERGY INTERNET INDUSTRY IN JIANGSU PROVINCE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
Energy Internet, an energy supply system that integrates electronic, information, and intelligent management technology, is important for future development. Considering the current regulation of energy consumption, multi-stakeholders expect an accelerated development of the energy Internet industry. With the successful development of 5G technology, energy Internet technology is regarded as one of the topics most likely to experience great success in the sustainable field. Previous research on Energy Internet has mainly focused on architectural innovation and utility evaluation, whereas not much focus has been put on the evolution and development of energy Internet enterprises. This paper analyzed enterprise data with ArcGIS and other geoscience software. Taking Jiangsu Province as an example, the present study explored the evolution of the spatial distribution pattern of the energy Internet over time. The results showed that from 2017 to 2021, the average nearest neighbor index of energy Internet enterprises in Jiangsu Province was 0.3494, indicating the significant presence of spatial agglomeration in the area.Furthermore, the degree of agglomeration has been increasing year by year. There was a large gap between cities in Jiangsu Province. In 2021, the number of energy Internet enterprises in Yangzhou was only a bit over one-eighth of Nanjing, and the gap was growing. The enterprise development center appeared in the southern part of Yangzhou City and tended to move to the northwest.
Keywords: Aeronautical reconnaissance coverage geographic information system (ArcGIS); 5G; Energy Internet; Industrial trend; Innovation